Aminosiloxane ester copolymers and methods for preparing and using copolymers
Patent Information
- Application Number
- JP2023579213
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-28
- Filing Date
- 2022-05-31
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2042-05-31
Smart Images

Figure 0007943874000001 
Figure 0007943874000002 
Figure 0007943874000003
Abstract
Description
[Technical Field]
[0001] (Cross-reference of related applications) This application asserts the interests of U.S. Provisional Patent Application No. 63 / 215533, filed on 28 June 2021, pursuant to Section 119(e) of the U.S. Patent Act. Provisional Patent Application No. 63 / 215533 is incorporated herein by reference.
[0002] (Field of invention) This invention relates to aminosiloxane ester copolymers useful for hair care applications. The invention further relates to a process for producing copolymers, emulsions containing copolymers, and methods for using copolymers and emulsions. [Background technology]
[0003] Introduction Amino-functional polyorganosiloxanes, such as amine-terminated polydiorganosiloxanes, are useful for hair care applications, such as hair conditioning. Amine-terminated polydiorganosiloxanes produced by condensation may have the drawback of instability, as indicated by viscosity changes and / or the generation of ammonia odor after aging, which is undesirable for hair care applications. Traditionally, the production of primary amine-terminated polyorganosiloxanes by equilibration is costly, as it requires expensive starting materials and catalysts and multiple process steps to complete.
[0004] Another method for producing amine-terminated polyorganosiloxanes involves using allylamine or derivatives that hydrolyze to allylamine. These are used to form amine-terminated polyorganosiloxanes by performing hydrosilylation chemistry with SiH-terminated polymers. However, this method has the drawback that the amine-terminated polyorganosiloxane product may contain at least trace amounts of either SiH or allylamine, which must be removed before the product can be used for any hair care application.
[0005] Another method for producing amine-terminated polyorganosiloxanes is by ammoniaxation of chloropropyl-terminated siloxanes. This expensive multi-step method has the drawback of potentially leaving residual salts (i.e., ammonium chloride) in the amine-terminated polyorganosiloxane product, which may require extensive washing to remove, making it less cost-effective and less sustainable. Furthermore, any residual ammonium chloride may produce an unpleasant odor, which is undesirable for hair care applications.
[0006] Acrylic-functional silicone compounds and methods for preparing them are disclosed in U.S. Patent No. 4,697,026 by Lee et al. Lee discloses that acrylic-functional silicon compounds can be prepared by tightly mixing an amino-functional silicon compound having at least one primary or secondary amine group with an acrylic-functional compound having at least two acrylate, methacrylate, acrylamide, or methacrylamide groups per molecule. There is a reaction in which mixing an amine compound with an acrylic compound produces an acrylic-functional silicon compound. This reaction is known as Michael addition. While we do not wish to be constrained by theory, the compounds described by Lee et al. are considered unsuitable for use in hair care applications because the acrylate functional groups of those compounds can be skin sensitizers and irritants, making them unsuitable for hair care applications where contact with the consumer's skin and potential accidental contact with the eyes may occur. [Overview of the project]
[0007] Aminosiloxane ester copolymers are formulated with the formula:
[0008] [ka] (In the formula, Each R 1 This is a monovalent hydrocarbon group consisting of 1 to 12 independently selected carbon atoms. Each R Eis independently selected from the group consisting of hydroxyl and the formula H2N-R A - amino functional group, each R A is independently a divalent hydrocarbon group having 1 to 12 carbon atoms, each R 2 is independently selected from the group consisting of H and methyl, each R D is an independently selected divalent hydrocarbon group having 2 to 20 carbon atoms, each subscript a independently has a value such that 0<a≦220, the subscript b has a value such that 1≦b≦100), is included.
[0009] The process for preparing the copolymer is 1) combining starting materials comprising (A) the formula
[0010]
Chemical Formula
[0011]
Chemical Formula
[0012] [ka] A bis-silanol-terminated polydiorganosiloxane, wherein R 1 And the subscript a is as described above, bis-silanol-terminal polydiorganosiloxane, and (G) formula
[0013] [ka] A cyclic siloxane in which the subscript c is 0 or 1, and each R 8 R is a monovalent hydrocarbon group of 1 to 18 independently selected carbon atoms, and each R 9 This may further involve independently preparing a starting material comprising a cyclic siloxane selected from the group consisting of hydrogen and an alkyl group with 1 to 15 carbon atoms.
[0014] Alternatively, the copolymer preparation process may further include combining (F) the bis-silanol-terminated polydiorganosiloxane described above, (B) the bis-acryloyloxy-alkane described above, and (G) the cyclic siloxazane described above.
[0015] The emulsion comprises (I) a liquid continuous phase containing water, and (II) a discontinuous phase dispersed in the liquid continuous phase, the discontinuous phase containing the above-mentioned aminosiloxane ester copolymer. The above-mentioned copolymer and / or emulsion is useful in hair care compositions. [Modes for carrying out the invention]
[0016] Aminosiloxane ester copolymers (copolymers) are given by the formula:
[0017] [ka] (In the formula, each R 1 R is a monovalent hydrocarbon group consisting of 1 to 12 independently selected carbon atoms, and each R E These are independently hydroxyl and formula H2N-R A - Selected from the group consisting of amino functional groups, each R A R is a divalent hydrocarbon group of 1 to 12 independently selected carbon atoms, and each R 2 Each R is independently selected from the group consisting of hydrogen and methyl, D (where a is an independent divalent hydrocarbon group of 2 to 20 carbon atoms, each subscript a independently has a value such as 0 ≤ a < 220, and the subscript b has a value such as 1 ≤ b ≤ 100), Includes.
[0018] R 1 Suitable monovalent hydrocarbon groups include alkyl, alkenyl, aryl, and combinations thereof (e.g., aralkyl and aralkenyl). For example, suitable alkyl groups include methyl, ethyl, propyl (including isopropyl and n-propyl), butyl (including isobutyl, n-butyl, sec-butyl, and tert-butyl), pentyl (including linear pentyl and / or cyclopentyl) and branched alkyl groups having 5 carbon atoms, hexyl (including linear hexyl and / or cyclohexyl) and branched alkyl groups having 6 carbon atoms, octyl (including linear octyl and / or cyclooctyl), branched alkyl groups having 8 carbon atoms, decyl (including linear decyl and / or cyclodecyl) and branched alkyl groups having 10 carbon atoms, and dodecyl (including linear dodecyl and / or cyclododecyl) and branched alkyl groups having 12 carbon atoms. Alternatively, R 1 The alkyl group may be selected from the group consisting of methyl and ethyl, or it may be methyl. 1Suitable alkenyl groups include vinyl, allyl, and hexenyl, or vinyl, hexenyl, or vinyl. 1 Suitable aryl groups may include cyclopentadienyl, phenyl, naphthyl, and anthracenyl. 1 Suitable aralkyl groups include tolyl, xylyl, benzyl, 1-phenylethyl, and 2-phenylethyl. Alternatively, R 1 The aryl group may be phenyl. Aralkyl groups such as benzyl, 1-phenylethyl and 2-phenylethyl groups, and aralkenyl groups such as styryl groups are also R 1 It may be used as such. Alternatively, each R 1 R may be selected from the group consisting of methyl and phenyl. Alternatively, each R 1 It may also be methyl.
[0019] Each R E These independently consist of a hydroxyl group and the formula H2N-R A - Selected from the group consisting of amino functional groups, where R A It is a divalent hydrocarbon group. Alternatively, each R E It may be a hydroxyl group. Alternatively, each R E The formula is H2N-R A - May also be an amino functional group. A R is a divalent hydrocarbon group that can be independently selected from 1 to 12 carbon atoms, 2 to 12 carbon atoms, 2 to 5 carbon atoms, or 2 to 3 carbon atoms. A The divalent hydrocarbon group may be linear, branched, cyclic, or a combination thereof. A Suitable divalent hydrocarbon groups include alkylene groups, arylene groups, and combinations thereof (e.g., dialkylarylene groups). Examples of alkylene groups include ethylene, propylene, and butylene. A The arylene group may be an arylene group such as phenylene. Alternatively, R A This is a dialkylarylene group, for example:
[0020] [ka] or
[0021] [ka] Examples of alkylarylene groups include those where each subscript u is independently 1-6 or 1-2. Alternatively, each R A This may be an alkylene group such as ethylene, propylene, or butylene. Alternatively, it may be ethylene.
[0022] Each R 2 Each R is independently selected from the group consisting of hydrogen and methyl. Alternatively, each R 2 It may be hydrogen.
[0023] Each R D R is a divalent hydrocarbon group consisting of 2 to 20 carbon atoms, or 2 to 12 carbon atoms, or 3 to 12 carbon atoms, or 4 to 12 carbon atoms, or 4 to 10 carbon atoms, independently selected. D The divalent hydrocarbon group may be linear, branched, cyclic, or a combination thereof. D Suitable divalent hydrocarbon groups include alkylene groups, arylene groups, and combinations thereof. Alternatively, each R D R may be an alkylene group such as propylene, butylene, hexylene, octylene, decylene, or dodecylene, or each R D may be butylene, hexylene, or decilen. Alternatively, R D R may be a branched alkylene group. D The arylene group may be an arylene group such as phenylene. Alternatively, R D teeth,
[0024] [ka] or
[0025] [ka] It may also be a dialkylarylene group, and in the formula, each subscript u is independently 1 to 6 or 1 to 2.
[0026] The subscript 'a' has a value such as 0 ≤ a < 220. Alternatively, the subscript 'a' may have a value between 2 and 200, or between 16 and 84, or between 16 and 44, or between 44 and 84.
[0027] The subscript b has a value such as 2 ≤ b ≤ 100. Alternatively, the subscript b may have a value between 2 and 20, or between 2 and 10.
[0028] The copolymer described above may have a number-average molecular weight (Mn) of >1,000 g / mol to 250,000 g / mol as measured by GPC according to the test method described below. Alternatively, the copolymer may have a Mn of 4,000 g / mol to 250,000 g / mol, or 4,000 g / mol to 100,000 g / mol as measured by GPC.
[0029] Alternatively, the copolymer described above may have a weight-average molecular weight (Mw) of 2,000 g / mol to 400,000 g / mol. Alternatively, Mw may be 10,000 g / mol to 390,000 g / mol, or 12,000 g / mol to 200,000 g / mol, or 15,000 g / mol to 185,000 g / mol, or 19,000 g / mol to 175,000 g / mol, or 20,000 g / mol to 100,000 g / mol, or 21,000 g / mol to 80,000 g / mol, or 22,000 g / mol to 75,000 g / mol, or 25,000 g / mol to 65,000 g / mol, or 30,000 g / mol to 60,000 g / mol, or 35,000 g / mol to 55,000 g / mol, or 40,000 g / mol to 50,000 g / mol.
[0030] Copolymer Manufacturing Process The copolymers mentioned above are 1) Formula (A)
[0031] [ka] A terminal primary amino-functional polyorganosiloxane, wherein R 1 , R A And the subscript a is as described above, terminal primary amino-functional polyorganosiloxane, and Formula (B)
[0032] [ka] A bis-acryloyloxyalkane in which R D As described above, the process may be adjusted by combining starting materials containing bis-acryloyloxy-alkane, wherein starting materials (A) and (B) are present in amounts such that the molar ratio of (A):(B) is in the range of 2:1 to 1:1.1, or 2:1 to 1:1.05, or 2:1 to 1:1. Alternatively, the molar ratio of (A):(B) may be at least 1:1, or at least 1.1:1, or at least 1.3:1, and at the same time, the ratio may be up to 2:1, or up to 1.8:1, or up to 1.5:1. The copolymer produced by this process has amino-functional ends, i.e., in the formula of the copolymer, each R E As mentioned above, formula H2N-R A - is an amino functional group.
[0033] The above process may optionally further include, during step 1), the addition of additional starting materials selected from the group consisting of (C) a catalyst, (D) a solvent, (E) an acrylate polymerization inhibitor, and two or more combinations of (C), (D), and (E).
[0034] Step 1) includes mixing the starting materials while optionally heating them. The mixing in Step 1) may be carried out for 1 to 48 hours, or 4 to 24 hours, or 6 to 15 hours. The temperature in Step 1) may be 0°C to 180°C, or 20°C to 160°C, or 60°C to 150°C, or 80°C to 120°C. The mixing (and heating) may be carried out by any convenient means, such as introducing the starting materials into a vessel such as a reaction distillation apparatus having a stirred jacketed batch reactor or a jacketed reboiler, and the jacket can be heated and cooled by passing steam / water or a heat transfer fluid through the jacket. Step 1) may be carried out under inert conditions such as less than 3% oxygen by purging the reactor with an inert gas such as nitrogen. For example, if Step 1) is operated above 60°C, it may be carried out in an atmosphere containing less than 3% oxygen. Alternatively, prior to heating in step 1), the process may optionally further include mixing the starting materials at room temperature for up to 60 minutes, or 5 to 30 minutes, or 15 to 30 minutes. While not intended to be constrained by theory, mixing at room temperature may facilitate the coalescence of the starting materials into one phase and initiate the reaction between (A) the terminal primary amino-functional polyorganosiloxane and (B) the bis-acryloyloxy-alkane. Furthermore, this additional mixing step may prevent or minimize polymerization of the acrylate groups.
[0035] The starting material (A) used in the above process is given by the formula:
[0036] [ka] It is a terminal primary amino-functional polyorganosiloxane, where R 1 , R A, and the subscript a are as described above. Preferred terminal primary amino-functional polyorganosiloxanes are exemplified by bis-3-aminopropyl-terminated polydimethylsiloxanes, which are commercially available, for example, from Milliken Chemical (Spartanburg, South Carolina, USA) under the trade name SiVance. Terminal primary amino-functional polyorganosiloxanes may also be prepared by known methods, such as those disclosed in U.S. Patent Application Publication No. 2004 / 0210074 by Hupfield et al., U.S. Patent No. 11,028,229 by Suthiwangcharoen et al., U.S. Patent No. 11,028,233 by Suthiwangcharoen et al., U.S. Patent No. 7,238,768 by Hupfield and U.S. Patent No. 8,796,198 by Henning et al.
[0037] The starting material (B) used in the above process is given by the formula:
[0038] [ka] It is a bis-acryloyloxy-alkane, where R D As stated above, suitable bis-acryloyloxyalkanes include 1,3-butanediol diacrylate, 1,4-butanediol diacrylate; 1,6-hexanediol diacrylate (also known as 1,6-bis(acryloyloxy)hexane); 1,9-bis(acryloyloxy)nonane; 1,10-decanediol diacrylate; and combinations thereof. Suitable bis-acryloyloxyalkanes are well known in the art and are commercially available from various suppliers, for example, Sigma-Aldrich, Inc. of St. Louis, Missouri, USA.
[0039] Starting material (C) is a catalyst that may be optionally added during the process described above. Although we do not wish to be constrained by theory, it is thought that the catalyst may facilitate the synthesis of the copolymer. If used, the catalyst is present in an amount >0 to <90% by weight based on the combined weight of starting materials (A) and (B). The exact amount of solvent depends on the type of catalyst selected. For example, if the catalyst is an alcohol, it can also be used as a solvent as described below, and the amount of catalyst may be greater than when using a different catalyst. For example, the alcohol may be used in an amount up to 90% based on the above, while the other catalysts described herein may be used in an amount >0 to <5% by weight based on the combined weight of starting materials (A) and (B).
[0040] The catalyst may include an alcohol, a tertiary amine, a pyridine, a pyridine derivative, or another aromatic heterocycle. Suitable alcohols include methanol, ethanol, isopropanol, butanol, n-propanol, and isofol-12 (2-butyl-octanol), isofol-20 (2-octyl-1-dodecanol), and INCI: octyldodecanol. While not intended to be theoretically constrained, longer-chain alcohols, such as isofol-12 (2-butyl-octanol), isofol-20 (2-octyl-1-dodecanol, INCI: octyldodecanol), may act as cosolvents for the resulting copolymer and may be incorporated into personal care compositions. These alcohols are commercially available from Sasol in Sandton, South Africa.
[0041] Suitable tertiary amines include trimethylamine, triethylamine, tributylamine, tetramethylethylenediamine, 1,8-diazabicyclo[5.4.0]-7-undecene (DBU), 1,5-diazabicyclo[4.3.0]nona-5-ene (DBN), 1,4-diazabicyclo[2.2.2]octane (DABCO), and 1,5,7-triazabicyclo[4.4.0]deca-5-ene (1,3,4,6,7,8-hexahydro-2H- Examples of suitable catalysts include pyrimido[1,2,-a]pyrimidine (also known as pyrimidine) (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]deca-5-ene (mTBD), N-(2-hydroxyethyl)piperazine, tetramethylguanidine (TMG), 1,2,2,6,6-pentamethylpiperidine, N-methylmorpholine (NMP), 2,2,6,6-tetramethylpiperidine (TMP), and 1-azabicyclo[2.2.2]octane. Preferred pyridine derivatives include dimethylpyridine, such as 2,6-dimethylpyridine (also known as 2,6-lutidine), and trimethylpyridine. The catalysts described above are commercially available from various suppliers, including Sigma Aldrich, Inc. and Fisher Scientific (Hampton, New Hampshire, USA).
[0042] The starting material (D) is a solvent that may be optionally added during the process described above. Suitable solvents include polydialkylsiloxanes, alcohols, aromatic hydrocarbons, aliphatic hydrocarbons, ethers, or combinations thereof. A polydialkylsiloxane with a suitable vapor pressure may be used as the solvent, such as hexamethyldisiloxane, octamethyltrisiloxane, hexamethylcyclotrisiloxane, dodecamethylcyclohexasiloxane, tetradecamethylcycloheptasiloxane, and other low molecular weight polyalkylsiloxanes such as DOWSIL® 200 Fluid and DOWSIL® OS Fluid, which are commercially available from DSC with a molecular weight of 0.5 to 1.5 cSt.
[0043] Alternatively, the starting material (D) may include an organic solvent. The organic solvent can be an alcohol such as methanol, ethanol, isopropanol, butanol, n-propanol, and aromatic hydrocarbons such as isofol-12 (2-butyl-octanol), isofol-20 (2-octyl-1-dodecanol), and INCI: octyldodecanol, benzene, toluene, or xylene; or an aliphatic hydrocarbon such as heptane, hexane, octane, or isododecane; or a combination thereof. Suitable organic solvents are commercially available from various suppliers, including Sigma-Aldrich, Inc. (St. Louis, Missouri, USA).
[0044] The solvent is optional. If present, the amount of solvent depends on various factors, including the type of solvent selected, as well as the amount and type of other starting materials selected for use in the process. However, if used, the amount of solvent may be 0% to 90% based on the total weight of all starting materials used in step (1). The solvent may be added, for example, to facilitate the mixing and delivery of one or more starting materials. For example, the catalyst may be delivered in the solvent. After step 1), all or part of the solvent may be optionally removed.
[0045] Starting material (E) is an acrylate polymerization inhibitor that may be optionally added during the process described above. If present, starting material (E), the inhibitor may be used in amounts >0 to <0.01% based on the combined weight of starting materials (A) and (B), or >0 to <10,000 ppm, or 1 ppm to 2,000 ppm, or 10 ppm to 500 ppm on the same basis. Suitable inhibitors are commercially available and include, for example, nitrobenzene, butylated hydroxyltoluene (BHT), diphenylpicrylhydrazyl (DPPH), p-methoxyphenol, 4-methoxyphenol (MEHQ), 2,4-di-t-butylcatechol, phenothiazine, salts of N,N-diethylhydroxylamine, N-nitrosophenylhydroxylamine, (2,2,6,6-tetramethylpiperidine-1-yl)oxidanil (TEMPO), and 4-hydroxy-(2,2,6,6-tetramethylpiperidine-1-yl)oxidanil (4-hydroxyTEMPO), phenothiazine (PTZ).
[0046] Those skilled in the art will recognize that certain starting materials may have two or more functions. For example, the alcohols mentioned above may function as both a catalyst and a solvent. Long-chain alcohols such as isofol-12 (2-butyl-octanol), isofol-20 (2-octyl-1-dodecanol, and INCI: octyldodecanol) may function as both a solvent and a emollient when the copolymer is incorporated into personal care products.
[0047] Alternatively, the copolymer mentioned above is 1) (B) The above-mentioned bis-acryloyloxyalkanes, (F) formula
[0048] [ka] A bis-silanol-terminated polydiorganosiloxane, wherein R 1And the subscript a is as described above, bis-silanol-terminal polydiorganosiloxane, and (G) formula
[0049] [ka] A cyclic siloxane in which the subscript c is 0 or 1, and each R 8 R is a monovalent hydrocarbon group consisting of 1 to 18 independently selected carbon atoms, and each R 9 A cyclic siloxane is independently selected from the group consisting of hydrogen and an alkyl group with 1 to 15 carbon atoms.
[0050] The preparation may be carried out by a process that includes combining starting materials containing the above. This process may optionally further include, during step 1), adding additional starting materials selected from the group consisting of (C) catalyst, (D) solvent, (E) acrylate polymerization inhibitor, and two or more combinations of (C), (D), and (E).
[0051] Step 1) includes mixing the starting materials while optionally heating them. The mixing in Step 1) may be carried out for 1 to 48 hours, or 4 to 24 hours, or 6 to 15 hours. The temperature in Step 1) may be 0°C to 180°C, or 20 to 160°C, or 60°C to 180°C, or 60°C to 150°C. The mixing (and heating) may be carried out by any convenient means, such as introducing the starting materials into a vessel such as a reaction distillation apparatus having a stirred jacketed batch reactor or a jacketed reboiler, and the jacket can be heated and cooled by passing steam / water or a heat transfer fluid through the jacket. Step 1) may be carried out under inert conditions such as less than 3% oxygen by purging the reactor with an inert gas such as nitrogen. For example, if Step 1) is operated above 60°C, it may be carried out in an atmosphere containing less than 3% oxygen.
[0052] The copolymer produced by this process is R in the above formula. E It has terminal groups indicated by . The choice of terminal groups depends on the amount of starting material used in the process. For example, if the molar equivalents of (B) bis-acryloyloxy-alkane, (F) bis-silanol-terminated polydiorganosiloxane, and (G) cyclic siloxane are such that less than 2 molar equivalents of (G) cyclic siloxane per mole of (F) bis-silanol-terminated polydiorganosiloxane, and 0.5 molar equivalents of (B) bis-acryloyloxy-alkane per mole of (G) cyclic siloxane are used, then each R in the formula of the aminosiloxane ester copolymer E (B) may be the aforementioned hydroxyl group. Furthermore, the amount of (B) bis-acryloyloxy-alkane may be less than 0.5 molar equivalents of (G) cyclic siloxazane in order to avoid residual acrylate functional groups present in the copolymer, thereby R E A part of the base is the above formula H2N-R A It is an amino functional group, R E Part of the group may be a hydroxyl group.
[0053] Alternatively, in the case of (G) cyclic siloxanes exceeding 2 molar equivalents per mole of (F) bis-silanol-terminated polydiorganosiloxane, each R E As mentioned above, formula H2N-R A -The amino functional group may be R. Alternatively, the copolymer produced by this process may have R in the same molecule. E One example of a group that is an amino functional group, and R E There may be one example where is a hydroxyl group. E The amount of amino functional groups in the copolymer is R E Based on the total molar amount, it may be 0-100%, 0-50%, or 0-5%.
[0054] The starting material (F), bis-silanol-terminated polydiorganosiloxane, and the starting material (B), bis-acryloyloxy-alkane, may be adjusted by a process involving combination, such that the molar ratio of (F):(B) is in the range of 2:1 to 1:1.1, or 2:1 to 1:1.05, or 2:1 to 1:1. Alternatively, the molar ratio of (F):(B) may be at least 1:1, or at least 1.1:1, or at least 1.3:1, while at the same time the ratio may be up to 2:1, or up to 1.8:1, or up to 1.5:1.
[0055] The starting material (F) is given by the formula:
[0056] [ka] A bis-silanol-terminated polydiorganosiloxane, wherein R 1 And the subscript a is as described above. Examples of starting materials (F) include bis-silanol-terminated polydimethylsiloxanes, which are known in the art and are commercially available, for example, from DSC under the trade name XIAMETER®OHX. Bis-silanol-terminated polydiorganosiloxanes suitable for use as starting materials (F) may be prepared by methods known in the art, such as hydrolysis and condensation of the corresponding organohalosilane, or equilibration of the cyclic polydiorganosiloxane.
[0057] The starting material (G) is given by the formula:
[0058] [ka] A cyclic siloxane in which the subscript c is 0 or 1, and each R 8 R is a monovalent hydrocarbon group consisting of 1 to 18 independently selected carbon atoms, and each R 9 Each R is independently selected from the group consisting of hydrogen and alkyl groups with 1 to 15 carbon atoms. 9R is independently selected from the group consisting of hydrogen and alkyl groups of 1 to 15 carbon atoms, 1 to 12 carbon atoms, or 1 to 6 carbon atoms. Preferred alkyl groups are exemplified by branched saturated monovalent hydrocarbyl groups of 6 or more carbon atoms, including methyl, ethyl, propyl (e.g., isopropyl and / or n-propyl), butyl (e.g., isobutyl, n-butyl, tert-butyl, and / or sec-butyl), pentyl (e.g., isopentyl, neopentyl, and / or tert-pentyl), hexyl, heptyl, octyl, nonyl, and decyl, and cycloalkyl groups such as cyclopentyl and cyclohexyl. Alternatively, R 9 Each alkyl group can be methyl. Alternatively, each R 9 This can be a hydrogen atom. Alternatively, at least one R per molecule. 9 This can be an alkyl group such as methyl.
[0059] Each R 8 R is an independently selected monovalent hydrocarbon group having 1 to 18 carbon atoms. Examples of monovalent hydrocarbon groups include alkyl groups, aryl groups, and aralkyl groups. Alternatively, the monovalent hydrocarbon group may be an alkyl group. 8 Examples include, 9 Examples are given.
[0060] Suitable examples of cyclic siloxanes include: formula
[0061] [ka] 1,1,3,3,-tetramethyl-2-oxa-7-aza-1,3-disilacycloheptane, and formula
[0062] [ka] One example is 1,1,3,3,5,5-hexamethyl-2,4-dioxa-9-aza-1,3,5-trisilacyclononane.
[0063] Cyclic siloxanes may be prepared by hydrosilylation of an allyl-functionalized amine with a SiH-terminated siloxane oligomer in the presence of a hydrosilylation catalyst and a hydrosilylation accelerator, as described in U.S. Provisional Patent Application No. 62 / 940414 filed November 26, 2019, by Rekken et al., incorporated herein by reference.
[0064] In the process described above, (B) bis-acryloyloxy-alkane, (F) bis-silanol-terminated polydiorganosiloxane, and (G) cyclic siloxazane may be combined simultaneously or in any order in step 1). Although we do not wish to be constrained by theory, when the starting materials (B), (F), and (G) are combined simultaneously, it is thought that the cyclic siloxazane (G) first reacts with the silanol group of the starting material (B) to form a terminal primary amino-functionalized polydiorganosiloxane in situ, which then undergoes aza-Michael addition with the bis-acryloyloxy-alkane (B). Surprisingly, the inventors found that the bis-acryloyloxy-alkane (B) does not readily react with the secondary amine functional group of the cyclic siloxazane. Alternatively, in step 1), starting material (G), a cyclic siloxane, and starting material (F), a bis-silanol-terminated polydiorganosiloxane, may be combined to form an amino-functional polyorganosiloxane, after which starting material (B), a bis-acryloyloxy-alkane, may be added. Although we do not wish to be constrained by theory, it is thought that (G) the cyclic siloxane does not readily react with (B) the bis-acryloyloxy-alkane. The process for forming (A) a terminal primary amino-functional polyorganosiloxane may include i) combining starting materials comprising (G) the cyclic polysiloxane described above and (F) the bis-silanol-terminated polydiorganosiloxane described above, and optionally ii) recovering (A) the primary amino-functional polyorganosiloxane. This process may also be carried out by selecting a bis-silanol-terminated polydiorganosiloxane corresponding to the above-mentioned starting material (F) for use in this method, as described in US Provisional Patent Application Serial No. 62 / 940414 filed by Rekken et al. on November 26, 2019.
[0065] Step 1) in the process for forming a primary amino-functional polyorganosiloxane (combining the starting materials comprising (G) and (F)) may be carried out by any convenient means, such as mixing with heating, which is of optional choice. Mixing and heating may be carried out using any convenient means, such as introducing the starting materials into a vessel such as a reaction distillation apparatus having a stirred jacketed batch reactor or a jacketed reboiler, and the jacket may be heated and cooled by passing steam / water or a heat transfer fluid through the jacket. The process may be carried out at a temperature of at least 50°C, or at least 85°C, or at least 90°C. Alternatively, the heating in step 1) may be carried out at 50°C to 150°C, or 85°C to 150°C, or 90°C to 150°C. The process is carried out for a sufficient amount of time to form the (A)-terminated primary amino-functional polyorganosiloxane. In step i), one of (G) a cyclic siloxane and (F) a bis-silanol-terminated polydiorganosiloxane may be added sequentially or incrementally to a container containing the other of (F) and (G). Such addition may be carried out manually or using a weighing instrument. The process for forming the (A) primary amino-functional polyorganosiloxane (A) described above may optionally further comprise one or more additional steps. This process may optionally further comprise step iii), in which one or more additional starting materials are added to the reaction mixture in step i). Alternatively, step iii) may be carried out during and / or after step i), and before step ii). Additional starting materials may be selected from the group consisting of acidic pre-catalysts, aminoalkyl-functionalized alkoxysilanes, end-capping agents, solvents, and combinations of two or more thereof, as described in U.S. Provisional Patent Application No. 62 / 940414 filed November 26, 2019, for starting material (D). The resulting primary amino-functionalized polyorganosiloxane may be used in the process described above to produce the aminosiloxane ester copolymer described above.
[0066] In the above-described process for producing aminosiloxane ester copolymers, this method may optionally include one or more additional steps. The process may further include 2) recovering the aminosiloxane ester copolymer (during and / or after step 2). Recovery may be carried out by any convenient means such as (C) removal of the catalyst by heating and optionally by stripping and / or distillation with reduced pressure, and / or by stripping and / or distillation, neutralization if a catalyst is used, and / or adsorption. Furthermore, those skilled in the art will recognize that, in the above-described process, when (G) cyclic siloxanes are used, the alcohol is not used as (C) catalyst and (D) solvent in the presence of (G) cyclic siloxanes to avoid the reaction of the alcohol with the cyclic siloxane to produce an alkoxy-functional amino-functional alkoxysilane or siloxane.
[0067] Emulsion containing copolymer The copolymers described above may be incorporated into the emulsion. The emulsion comprises (I) a liquid continuous phase containing water and (II) a discontinuous phase dispersed in the liquid continuous phase, the discontinuous phase may contain the aminosiloxane ester copolymer described above. The amount of copolymer added to the emulsion can vary and is not limited. However, the amount may typically be in the range of 1 to 70%, or 2 to 60% copolymer / emulsion by weight ratio. Water (and additional starting materials, if present) may constitute the remainder of the emulsion up to 100%.
[0068] water Water can be used in any form, generally undiluted (i.e., without any carrier vehicle / solvent) and / or pure (i.e., free from or substantially free from minerals and / or other impurities). For example, water may be treated or untreated before producing the emulsion described above. Examples of processes that may be used to purify water include distillation, filtration, deionization, and two or more combinations thereof, thereby performing deionization, distillation, and / or filtration on the water. Alternatively, water may be untreated (e.g., tap water, i.e., water from a city water system, or well water used without further purification). Or, water may be purified before being used to produce the emulsion.
[0069] Additional starting materials The emulsion described above may further contain additional starting materials selected from the group consisting of (H) surfactants, (I) acid compounds, (J) acid anhydrides, (K) thickeners, (L) stabilizers, (M) preservatives, and two or more combinations of (H), (I), (J), (K), (L), and (M).
[0070] The copolymer described above may be self-emulsifying (i.e., a separate surfactant is optional). However, if a surfactant is used, it may be anionic, cationic, nonionic, amphoteric, or a combination of two or more of these. The amount of surfactant may be 2% to 25% based on the total weight of all starting materials in the emulsion.
[0071] (H) Surfactants Anionic surfactants may be selected from alkali metal sulforicinates, sulfonated glyceryl esters of fatty acids, salts of sulfonated monohydric alcohol esters, amides of aminosulfonic acids, sulfonation products of fatty acid nitriles, sulfonated aromatic hydrocarbons, condensation products of naphthalenesulfonic acid and formaldehyde, sodium octahydroanthracenesulfonate, sodium lauryl sulfate, alkali metal alkyl sulfates, alkyl ether sulfates having at least 8 carbon atoms, alkylaryl ether sulfates, alkylaryl sulfonates having at least 8 carbon atoms, alkylbenzenesulfonic acids, salts of alkylbenzenesulfonic acids, sulfates of polyoxyethylene alkyl ethers, amine salts or sodium or potassium salts of alkylnaphthylsulfonic acids, and combinations thereof. Suitable anionic surfactants are commercially available from various suppliers, including sodium lauryl sulfate, which is available from Pilot under the trade name CALIMULSE® SLS. Other anionic surfactants commercially available from TDCC include alkyl diphenyl oxide disulfate available under the trade name DOWFAX®, dioctyl sulfosuccinate available under the trade name TRITON® GR, phosphate esters available under the trade names TRITON® H-55, H-65, QS-44, or XQS-20, and sulfates and sulfonates available under the trade names TRITON® QS-15 and TRITON® XN-45S.
[0072] Cationic surfactants may be selected from dodecylamine acetate, octadecylamine acetate, acetates of amines of tallow fatty acids, homologs of aromatic amines having fatty acids, fatty amides derived from aliphatic diamines, fatty amides derived from aliphatic diamines, fatty amides derived from disubstituted amines, derivatives of ethylenediamines, quaternary ammonium compounds, salts of quaternary ammonium compounds, alkyltrimethylammonium hydroxide, dialkyldimethylammonium hydroxide, coconut oil, methylpolyoxyethylene cocoammonium chloride, dipalmitoylethylhydroxyethylmonium methosulfate, amide derivatives of amino alcohols, amine salts of long-chain fatty acids, and combinations thereof. Cationic surfactants are commercially available from various suppliers, including Akzo Nobel's ARQUAD® branded dialkylmethylquaternary ammonium compounds (e.g., cetrimonium chloride), Evonik's ADOGEN® cationic surfactants, Tomah Products, Inc. (Milton, Wisconsin, USA)'s TOMAH® cationic surfactants, and Sea-Land Chemical Company (Westlake, Ohio, USA)'s VARIQUAT® cationic surfactants.
[0073] Nonionic surfactants may be selected from alkylphenol alkoxylates, ethoxylated and propoxylated aliphatic alcohols, alkyl polyglucosides and hydroxyalkyl polyglucosides, sorbitan derivatives, N-alkyl glucamides, alkylene oxide block copolymers, such as ethylene oxide, propylene oxide and / or butylene oxide block copolymers, aliphatic alcohol polyglycol ethers, polyhydroxy and polyalkoxy aliphatic derivatives, amine oxides, silicone polyethers, and various polymer surfactants. Nonionic surfactants are commercially available; for example, alkylphenol alkoxylates are available under the trade name ECOSURF® EH, secondary alcohol ethoxylates, nonylphenol ethoxylates, and ethylene oxide / propylene oxide copolymers are available under the trade name TERGITOL®, and specialty alkoxylates such as amine ethoxylates and octylphenol ethoxylates are available under the trade name TRITON®, all from TDCC. Alternatively, the nonionic surfactant may be, for example, trideceth-6 or trideceth-12, available from Croda under the trade name SYNPERONIC® or from BASF under the trade name LUTENSOL®. Alternatively, the nonionic surfactant may be a fatty alcohol polyglycol ether such as GENAPOL® UD050 and GENAPOL® UD110, commercially available from Clariant (Frankfurt, Germany).
[0074] Nonionic surfactants may also be silicone polyethers (SPEs). Silicone polyethers as emulsifiers may have a rake-shaped structure in which polyoxyethylene or polyoxyethylene-polyoxypropylene copolymer units are grafted onto a siloxane main chain, or SPEs may have an ABA block copolymer structure in which A represents the polyether portion and B represents the siloxane portion of the ABA structure. A suitable silicone polyether is DSC's Dow Silicones™ 5329. Alternatively, nonionic surfactants may be selected from polyoxyalkylene-substituted silicones, silicone alkanolamides, silicone esters, and silicone glycosides. Such silicone-based surfactants are known in the art and are described, for example, in U.S. Patent No. 4,122,029 by Gee et al., U.S. Patent No. 5,387,417 by Rentsch, and U.S. Patent No. 5,811,487 by Schulz et al.
[0075] Suitable amphoteric surfactants include betaines such as alkyl (C12-14) betaine, cocoamidopropyl betaine, cocoamidopropyl dimethyl-hydroxysulfobetaine, dodecylbetaine, hexadecylbetaine, and tetradecylbetaine; sultaines such as cocamidopropyl hydroxysultaine; lecithin, hydrogenated lecithin, cocoamphodiacetate, cocoiminodipropionate, and dodecyliminodipropionate.
[0076] The emulsion may be formed as a water-in-oil (w / o) emulsion containing a water-in-oil surfactant (which may then be reversed by the addition of further water). The water-in-oil surfactant may be nonionic and may be selected from polyoxyalkylene-substituted silicones, silicone alkanolamides, silicone esters, and silicone glycosides, as described above. Alternatively, if the emulsion is an oil-in-water (o / w) emulsion, the emulsion may contain a nonionic surfactant known in the art to prepare an o / w emulsion. Suitable nonionic surfactants for this embodiment are exemplified by polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene lauryl ethers, polyoxyethylene sorbitan monooleate, polyoxyethylene alkyl esters, polyoxyethylene sorbitan alkyl esters, polyethylene glycol, polypropylene glycol, ethylene glycol, ethoxylated trimethylnonanol, and polyoxyalkylene glycol-modified polysiloxane surfactants, as described above.
[0077] (I) Acid compound Acid compounds may be optionally added to the emulsions described herein to adjust the pH. Suitable acids include acetic acid, formic acid, propionic acid, and combinations thereof. Suitable acids for adjusting pH are disclosed, for example, in U.S. Patent No. 6,180,117.
[0078] Emulsion manufacturing method Emulsions may be prepared in batch, semi-continuous, or continuous processes using conventional equipment. For example, mixing of starting materials to form an emulsion may occur using equipment such as batch equipment with high shear and high-speed dispersers, including those manufactured by Charles Ross & Sons (NY) and Hockmeyer Equipment Corp. (NJ), such as batch mixing equipment sold under the trade name Speedmixer®, or batch equipment that performs high shear action, including Banbury type (CW Brabender Instruments Inc., NJ) and Henschel type (Henschel mixers America, TX). Exemplary examples of continuous mixers / compounders include single-screw extruders, twin-screw extruders, and multi-screw extruders, co-rotating extruders, twin-screw counter-rotating extruders, two-stage extruders, twin-screw rotary continuous mixers, dynamic or static mixers, or combinations thereof, such as those manufactured by Krupp Werner & Pfleiderer Corp (Ramsey, NJ) and Leistritz (NJ).
[0079] The above-mentioned starting materials may be combined under any suitable conditions for forming an emulsion. For example, to simplify the mixing process and keep the emulsion viscosity low during handling, any acid compound may be added at the end of the method, i.e., once the desired dilution level is reached.
[0080] hair care Copolymers and emulsions containing copolymers are useful in hair care compositions, as described above. The hair care composition may also be a conditioner and / or leave-in hair treatment, such as a styling product. The hair care composition can be used for purposes such as styling (e.g., curl retention) and / or conditioning of hair fibers.
[0081] In using the hair care composition according to the present invention, conventional methods for conditioning hair may be used. For example, an effective amount of the composition for conditioning hair is applied to the hair. Such an effective amount is generally in the range of 0.5 g to 50 g, or alternatively, 1 g to 20 g. Application to the hair typically involves allowing the composition to act on the entire hair so that most or all of the hair is in contact with the product. This method for hair conditioning includes the steps of applying an effective amount of the hair care composition to the hair and then allowing the composition to act on the entire hair. These steps can be repeated as many times as desired to achieve the desired conditioning effect.
[0082] In addition to the copolymers and / or emulsions described above, non-limiting examples of additives that may be incorporated into the hair conditioner composition include: (i) chelating agents, (ii) deposition agents such as cationic deposition aids, (iii) additional emulsifiers (e.g., nonionic), (iv) fragrances, (v) oils, (vi) pigments, (vii) preservatives, (viii) stabilizers, (ix) thickeners, and combinations thereof.
[0083] The hair care composition may contain at least one cationic deposition aid or cationic deposition polymer. The cationic deposition aid may be present in an amount of 0.001% to 5%, or 0.01% to 1%, or 0.02% to 0.5% based on the total weight of all ingredients in the personal care product. The cationic deposition polymer may be a homopolymer or may be produced from two or more monomers. The molecular weight of the cationic deposition polymer may be at least 10,000, or in the range of 5,000 to 10,000,000, or 100,000 to 2,000,000. The cationic deposition polymer has cationic nitrogen containing a group such as a quaternary ammonium or a protonated amino group, or a mixture thereof. The cationic charge density may be at least 0.1 meq / g, or 0.8 meq / g or more. The cationic charge density shall not exceed 4 meq / g, nor shall it be less than 3, and or less than 2 meq / g. The charge density can be measured using the Kjeldahl method and must be within the above limits at the desired pH in use, which may be in the range of 3 to 9, or 4 to 8. Cationic nitrogen-containing groups generally exist as substituents on the fraction of all monomer units of the cationic deposition polymer. Therefore, if the cationic deposition polymer is not a homopolymer, it may contain non-cationic spacer monomer units. Such polymers are listed in the CTFA Cosmetic Ingredient Directory, 3rd edition. Suitable cationic adhesion aids include copolymers of cationic amines or vinyl monomers having quaternary ammonium functionality, such as (meth)acrylamide, alkyl and dialkyl(meth)acrylamide, alkyl(meth)acrylate, vinylcaprolactone, and vinylpyrrolidine, with water-soluble spacer monomers. Alkyl and dialkyl-substituted monomers may have alkyl groups of 1 to 7 carbon atoms, or alkyl groups of 1 to 3 carbon atoms. Other suitable spacers include vinyl esters, vinyl alcohols, maleic anhydride, propylene glycol, and ethylene glycol.Cationic amines can be primary, secondary, or tertiary amines, depending on the specific species and pH of the composition. Generally, secondary and tertiary amines, or quaternary amines, may be used. Amine-substituted vinyl monomers and amines can be polymerized in amine form and then converted to ammonium by quaternization. Suitable cationic amino and quaternary ammonium monomers include, for example, vinyl compounds substituted with dialkylaminoalkyl acrylates, dialkylaminoalkyl methacrylates, monoalkylaminoalkyl acrylates, monoalkylaminoalkyl methacrylates, trialkylmethacrylatexalkylammonium salts, trialkylacryloxalkylammonium salts, diallyl quaternary ammonium salts, and vinyl quaternary ammonium monomers having cyclic cationic nitrogen-containing rings such as pyridinium, imidazolium, and quaternary pyrrolidines, e.g., alkylvinylimidazolium, and quaternary pyrrolidines, e.g., alkylvinylimidazolium, alkylvinylpyridinium, and alkylvinylpyrrolidine salts. The alkyl portion of these monomers may be a lower alkyl group, such as an alkyl group with 1 to 4 carbon atoms or an alkyl group with 1 to 2 carbon atoms. Suitable amine-substituted vinyl monomers for use herein include dialkylaminoalkyl acrylates, dialkylaminoalkyl methacrylates, dialkylaminoalkylacrylamides, and dialkylaminoalkyl methacrylamides. Cationic deposition aids may include mixtures of monomer units derived from amine and / or quaternary ammonium-substituted monomers and / or compatible spacer monomers.Suitable cationic deposition aids include, for example: a copolymer of 1-vinyl-2-pyrrolidine and 1-vinyl-3-methylimidazolium salt (e.g., chloride salt) (known in the industry as polyquaternium-16 by the Cosmetic, Toiletry, and Fragrance Association, "CTFA"), such as that commercially available from BASF Wyandotte Corp. (Parsippany, NJ, USA) under the trademark name LUVIQUAT (e.g., LUVIQUAT FC 370); and a copolymer of 1-vinyl-2-pyrrolidine and dimethylaminoethyl methacrylate (known in the industry as polyquaternium-11 by the CTFA), such as that commercially available from Gar Corporation (Wayne, NJ, USA) under the trademark name GAFQUAT (e.g., GAFQUAT FC 370). Examples include those commercially available under the name 755N; cationic diallyl quaternary ammonium-containing polymers, such as dimethyldiallylammonium chloride homopolymers and copolymers of acrylamide and dimethyldiallylammonium chloride, known in the CTFA as polyquaternium 6 and polyquaternium 7, respectively; mineral salts of aminoalkyl esters of homopolymers and copolymers of unsaturated carboxylic acids having 3 to 5 carbon atoms, as described in U.S. Patent No. 4,009,256 (Nowak Jr., et al.); and cationic polyacrylamides as described in U.S. Patent No. 5,543,074 (Hague et al.). Other cationic adhesion aids that can be used include polysaccharide polymers such as cationic cellulose derivatives and cationic starch derivatives. Suitable cationic polysaccharide polymer materials for use in the compositions of the present invention include those of formula -O(R. 15 -N+R 16 R 17 R 18 X-) (wherein A is anhydrous glucose residue, for example, starch or cellulose anhydrous glucose residue, R 15 R is an alkylene oxyalkylene, polyoxyalkylene, or hydroxyalkylene group, or a combination thereof. 16 , R 17 , and R 18are each independently an alkyl, aryl, alkylaryl, arylalkyl, alkoxyalkyl, or alkoxyaryl group, each group containing no more than 18 carbon atoms, and the total number of carbon atoms in each cationic moiety (i.e., R 16 , R 17 , and R 18 the total number of carbon atoms therein) may be 20 or less, and X is an anionic counterion as described above). Cationic cellulose is commercially available from Amerchol Corp. (Edison, NJ, USA) as salts of hydroxyethyl cellulose reacted with trimethylammonium-substituted epoxides, the polymers of the Polymer JR™ and LR™ series, referred to in the industry (CTFA) as Polyquaternium 10. Another class of cationic celluloses includes polymeric quaternary ammonium salts of hydroxyethyl cellulose reacted with lauryldimethylammonium-substituted epoxide, referred to in the industry (CTFA) as Polyquaternium 24. These materials are commercially available from Amerchol Corp. (Edison, NJ, USA) under the trade name Polymer LM-200. Other cationic deposition aids that can be used include cationic guar gum derivatives such as guar hydroxypropyltrimonium chloride (commercially available from Celanese Corp. under the Jaguar™ series). Other materials include quaternary nitrogen-containing cellulose ethers (e.g., those described in U.S. Pat. No. 3,962,418 to Birkofer, which is incorporated herein by reference), as well as copolymers of etherified cellulose and starch (e.g., those described in U.S. Pat. No. 3,958,581 to Abegg et al., which is incorporated herein by reference).
[0084] Hair care compositions may contain various additional oils. As used herein, the term “oil” refers to any material that is substantially water-insoluble. Suitable oils include, but are not limited to, natural oils such as coconut oil, hydrocarbons such as mineral oil and hydrogenated polyisobutene, fatty alcohols such as octyldodecanol and cetearyl alcohol (commercially available under the trade name Crodacol CS-50); esters such as C12-C15 alkyl benzoates, diesters such as propylene dipelargonate, triesters such as glyceryl trioctanoate, and silicones, particularly cyclomethicone and dimethicone, and combinations thereof. Hair care compositions may also contain oils, or mixtures of low-viscosity and high-viscosity oils. Suitable low-viscosity oils have a viscosity of 5-100 mPa.s at 25°C and structure R 20 CO-OR 21 [In the formula, R 20 CO represents a carboxylic acid group, OR 21The esters may have an alcohol residue. Examples of these low-viscosity oils include isotridecyl isononanoate, PEG-4 diheptanoate, isostearyl neopentanoate, tridecyl neopentanoate, cetyl octanoate, cetyl palmitate, cetyl lycinoleate, cetyl stearate, cetyl myristate, coco-dicaprylate / caprate, decyl isostearate, isodecyl oleate, isodecyl neopentanoate, isohexyl neopentanoate, octyl palmitate, dioctyl malate, tridecyl octanoate, myristyl myristate, octododecanol, or mixtures of octyldodecanol, acetylated lanolin alcohol, cetyl acetate, isododecanol, polyglyceryl-3-diisostearate, or mixtures thereof. High-viscosity surface oils generally have a viscosity of 200 to 1,000,000 mPa.s or 100,000 to 250,000 mPa.s at 25°C. Examples of surface oils include castor oil, lanolin and lanolin derivatives, triisocetyl citrate, sorbitan sesquioleate, C10-18 triglycerides, caprylic / capric / triglyceride, coconut oil, corn oil, cottonseed oil, glyceryl triacetyl hydroxystearate, glyceryl triacetyl ricinoleate, glyceryl trioctanoate, hydrogenated castor oil, linseed oil, mink oil, olive oil, palm oil, illipe oil, rapeseed oil, soybean oil, sunflower seed oil, taro, tricaprin, trihydroxystearin, triisostearin, trilaurin, trilinolein, trimyristine, triolein, tripalmitine, tristearin, walnut oil, wheat germ oil, cholesterol, or mixtures thereof. Alternatively, argan oil may be used. The recommended ratio of low-viscosity oil to high-viscosity oil in the oil phase is 1:15 to 15:1, or 1:10 to 10:1, respectively. Alternatively, personal care products may contain a mixture of 1% to 20% low-viscosity oil and high-viscosity oil.
[0085]
[0064] Among additional oils, for example, mineral oils such as liquid paraffin or liquid petroleum, animal oils such as perhydrosqualene, or vegetable oils such as sweet almond, calophyllum, palm, castor, avocado, jojoba, olive or cereal germ oil may be added to the hair care composition containing the above-mentioned copolymer. For example, esters of lanolic acid, oleic acid, lauric acid, stearic acid, or myristic acid; alcohols such as oleyl alcohol, linoleyl or linolenyl alcohol, isostearyl alcohol, or octyldodecanol; or acetyl glycerides, octanoates, decanoates, or ricinoleates of alcohols or polyalcohols can also be used. Alternatively, hydrogenated oils that are solid at 25°C, such as hydrogenated castor oil, palm oil, or coconut oil, or hydrogenated tallow; mono-, di-, tri-, or sucroglycerides; lanolin; or aliphatic esters that are solid at 25°C can be used.
[0086] Thickeners may be added to provide a convenient viscosity. For example, 500 mm at 25°C 2 / s to 25,000 mm 2 / s, or 3,000 to 7,000 mm 2A viscosity of 1 / s is generally preferred. Suitable thickeners include cellulose derivatives exemplified by sodium alginate, gum arabic, polyoxyethylene, guar gum, hydroxypropyl guar gum, ethoxylated alcohols, e.g., laureth-4 or polyethylene glycol 400, methylcellulose, methylhydroxypropylcellulose, hydroxypropylcellulose, polypropylhydroxyethylcellulose, hydroxyethylcellulose, starch and starch derivatives exemplified by hydroxyethyl amylose and starch amylose, locust bean gum, electrolytes exemplified by sodium chloride and ammonium chloride, and sugars such as fructose and glucose, and derivatives of sugars, e.g., PEG-120 methyl glucose diolate, or mixtures of two or more of these. Alternatively, the thickener may be selected from cellulose derivatives, sugar derivatives, and electrolytes, or from combinations of two or more of the above thickeners exemplified by combinations of cellulose derivatives and any electrolyte, and starch derivatives and any electrolyte. Thickening agents are commercially available; for example, hydroxyethylcellulose is available from TDCC under the trade name Cellosize® Hydroxyethylcellulose PCG-10 Europe. The thickening agent is 500 mm 2 / s~25,000mmm 2 It may be used in the hair care composition in an amount sufficient to provide a viscosity of / s. Alternatively, the thickener may be present in an amount of 0.05% to 10%, or 0.05% to 5%, based on the total weight of the hair care composition.
[0087] Stabilizers can be used in the aqueous phase of the hair care composition containing the copolymer described above. Suitable aqueous phase stabilizers may include, alone or in combination, one or more electrolytes, polyols, alcohols such as ethyl alcohol, and hydrophilic colloids. Typical electrolytes include alkali metal salts and alkaline earth salts, particularly sodium, potassium, calcium, and magnesium chloride salts, borates, citrates, and sulfates, as well as aluminum chlorohydrate, and polymer electrolytes, particularly hyaluronic acid and sodium hyaluronate. If the stabilizer is an electrolyte, or contains an electrolyte, it may amount to about 0.1% to 5% by weight, or 0.5% to 3% by weight, of the total composition. Hydrocolloids include gums such as xanthan gum or bee gum, and thickeners such as carboxymethylcellulose. Polyols such as glycerin, glycol, and sorbitol can also be used. Alternative polyols are propylene glycol, sorbitol, and butylene glycol. If a large amount of polyol is used, it is not necessary to add an electrolyte. However, it is common to use a combination of electrolytes, polyols, and hydrophilic colloids, such as magnesium sulfate, butylene glycol, and xanthan gum, to stabilize the aqueous phase.
[0088] The hair care composition may optionally further contain a chelating agent, such as tetrasodium ethylenediaminetetraacetate (tetrasodium EDTA), which is commercially available under the trade name Versene 220.
[0089] The hair care composition may optionally further contain additional emulsifiers. These additional emulsifiers may be nonionic emulsifiers, such as PEG-100 stearate and glyceryl stearate.
[0090] The hair care composition may optionally further contain preservatives. Examples of suitable preservatives include phenoxyethanol and methylisothiazolinone, which are commercially available as Neolone PE Preservative.
[0091] Hair care compositions can also be in the form of aerosols combining propellant gases such as carbon dioxide, nitrogen, and nitrous oxide, volatile hydrocarbons such as butane, isobutane, or propane, and chlorinated or fluorinated hydrocarbons such as dichlorodifluoromethane and dichlorotetrafluoroethane or dimethyl ether.
[0092] When selecting the components of the hair care composition described above, there may be overlap in the types of components, as certain components described herein may have more than one function. For example, hydroxyethylcellulose may be useful as a colloidal stabilizer and thickener. When additional components are added to the hair care composition, these additional components may be different from each other.
[0093] Alternatively, hair care products are (I) The copolymer described above, or an emulsion of the copolymer described above, (II) Water; (ix) optional thickener (e.g., hydroxyethyl cellulose), (v) Fatty alcohols (e.g., cetearyl alcohol) and other oils, (iii) Optionally, other emulsifiers (e.g., PEG-100 stearate and glyceryl stearate), (vii) Preservatives, and (ii) Cationic deposition aid, and The hair conditioner may optionally contain (i) a chelating agent (e.g., tetrasodium ethylenediaminetetraacetate).
[0094] Alternatively, the emulsion described above may be used as a leave-in hair treatment composition (e.g., a styling aid). [Examples]
[0095] The following examples are intended to illustrate the present invention and should not be construed as limiting the scope of the invention as defined in the claims. The specific starting materials used in the examples are listed in Table 1 below, followed by the characterization and evaluation procedures also used in the examples.
[0096] [Table 1]
[0097] As used herein, the material bearing the trademark XIAMETER® is commercially available from DSC.
[0098] In this Reference Example 1, the copolymer was prepared as follows: A terminal primary amino-functional polyorganosiloxane and a bis-(acryloyloxy)alkane were combined and mixed for 30 minutes under an inert atmosphere (i.e., oxygen content <3%). The resulting mixture was heated to 80-90°C for 1 hour. The mixture was then heated to 90-120°C and stirred for a set time (A time in Table 2 below) at an optional rate. The mixture was then heated to 130-150°C and stirred for a set time (B time in Table 2 below) at an optional rate. Examples 1p and 1q demonstrated that even if residual acrylate remained after heating, the acrylate was consumed over several days or weeks at ambient temperature. The resulting copolymer was then prepared as follows: 1 1H NMR, 13 1C NMR, 29 The samples were characterized by a combination of Si NMR, IR, rheometry (viscosity), and / or GPC. Evaluation of the storage modulus (G') and loss modulus with respect to frequency ωrad / s showed no cross-linking in the most acrylate-rich example (1a), indicating little to no polymer cross-linking.
[0099] [Table 2] 1 This indicates that sample 1p was mixed at ambient temperature for a further 4 days.2 This indicates that sample 1q was mixed at ambient temperature for a further 25 days. 3 This shows that the sample had a viscosity of 702 when first tested and a viscosity of 4572 after aging for two years. The data in Table 1 show that copolymers can be produced without a catalyst according to the method of the present invention illustrated by the procedure of Reference Example 1. The storage modulus and loss modulus data show that the copolymer is linear and does not suffer from the crosslinking drawback, which is a problem with amine-containing hydrocarbon polymers that form the polymer backbone of comparative examples using the Aza-Michael addition reaction with bis(acryloyloxy)alkanes.
[0100] In this comparative example 2, TAS4 was combined with BAA1. These two liquids were miscible when mixed at ambient temperature for 30 minutes, and then a catalytic amount of approximately 400 ppm of 2,6-lutidine was added. The resulting reaction mixture was heated at 80°C for 2 hours, then at 90°C for 5.5 hours to obtain a clear solution, which was cooled to ambient temperature and stirred. However, within 24 hours, the mixture disintegrated, yielding a suspension of solid polymerized acrylate and terminal amino-functionalized polydimethylsiloxane.
[0101] In Comparative Example 3, Comparative Example 2 was repeated, and a DBU catalyst was added to one of the batches, dividing it into two. Within 30 hours, both mixtures disintegrated, yielding a suspension of solid polymerized acrylate and terminal amino-functionalized polydimethylsiloxane.
[0102] Comparative Examples 2 and 3 showed that when terminal primary amino-functional polyorganosiloxanes with excessively high DP were used, copolymer formation was not possible under the tested conditions.
[0103] In this Reference Example 4, the copolymer was prepared as follows: A terminal primary amino-functional polyorganosiloxane and a bis-(acryloyloxy)-alkane were combined and mixed for 30 minutes under an inert atmosphere (i.e., oxygen content <3%). The catalyst (2,6-lutidine) was added, and the resulting mixture was heated to 90°C for 1 hour. The mixture was then heated to 110°C and stirred for a set time of any choice (mixing time A in Table 3 below). The mixture was then heated to 140°C-150°C and stirred for a set time of any choice (time B in Table 3 below). If residual acrylate is still present in the resulting product, it will be consumed over time under ambient conditions. The resulting copolymer was then prepared. 1 1H NMR, 13 1C NMR, 29 The samples were characterized by a combination of Si NMR, IR, rheometry (viscosity), and / or GPC.
[0104] [Table 3] 1 This indicates that, instead of heating as described above, sample 4a was held at 90°C for 13 hours. After heating, a considerable amount of residual acrylate was present, but after being left for 22 months, the viscosity of the material increased. 2 Sample 4f was too viscous to be measured using the same instrument as the other samples. After aging for 21 months, sample 4f became fibrous. Sample 4f had MW=389,121, Mn=41462, and PD=9.39.
[0105] In this Example 5, 45.00 g (113 mmol) of bis(aminopropyl)tetrasiloxane and 1,13-diamino-4,4,6,6,8,8,10,10-octamethyl-5,7,9-trioxa-4,6,8,10-tetracilatridecane were added to a 250 mL reaction flask equipped with a magnetic stirring rod and a thermocouple. The flask was inactivated, and 19.74 g (87 mmol) of BAA1 was added over 15 minutes under a stream of N2. Due to the exothermic reaction, the temperature of the mixture rose from approximately 22°C to 39°C, and the colorless, transparent liquid became significantly viscous. The mixture was stirred at ambient temperature for a further approximately 8 hours. 1 H, 13 C, and 29 Si NMR analysis confirmed the consumption of acrylate (BAA1). GPC revealed that the weight-average molecular weight of this substance was 4130 g / mol. This example demonstrates that the process to (AB)n copolymer using siloxane oligomer (DP=2) can be carried out using the method of the present invention without external heating. Significant exothermic reaction was observed, and the prepared product was more viscous (4150 mPa·s) compared to products prepared using TAA with DP=16 or DP=44.
[0106] (AB) nWe developed a three-component single-reactor process for producing copolymers. The process involved adding a bis-silanol-terminated polydiorganosiloxane, a bis-acryloyloxy-alkane, and a cyclic siloxazane (1,1,3,3-tetramethyl-2-oxa-7-aza-1,3-disilacycloheptane), as shown in Scheme 1 below, to form copolymers similar to those described in Reference Examples 1 and 4. Although we do not wish to be constrained by theory, it is thought that the cyclic siloxazane first reacts with the bis-silanol-terminated polydiorganosiloxane to form a bis(aminopropyl)siloxane in situ, and then undergoes aza-Michael 1,4-addition with the bis-acryloyloxy-alkane. Surprisingly, the bis-acryloyloxy-alkane used under the tested conditions did not readily react with the secondary amines present in the cyclic siloxazane. When cyclic siloxanes and bis-acryloyloxy-alkanes were combined in a mixture, no reaction was observed even after heating to 60°C for about 3 hours in the presence of 1.2% 2,6-lutidine catalyst. The cyclic siloxanes initiate a reaction with bis-silanol-terminated polydiorganosiloxanes, which terminates quickly within 6–8 hours at ambient temperature, and less at higher temperatures, as disclosed in International Publication No. 2021 / 108068, corresponding to U.S. Provisional Patent Application No. 62 / 940414 filed November 26, 2019 by Rekken et al. Although we do not wish to be bound by theory, the method provided herein is thought to involve the initial addition of a cyclic siloxane to a bis-silanol-terminated polydiorganosiloxane, followed by the addition of Aza-Michael, as shown in Scheme 1 below.
[0107] Scheme 1. (Top) The addition of cyclic siloxanes did not readily react with bis-acryloyloxy-alkanes. (Bottom) In the mixture, bis-silanol-terminated polydiorganosiloxanes react with cyclic siloxanes, regardless of the order of addition, and subsequently with bis-acryloyloxy-alkanes.
[0108] [ka]
[0109] In this Example 6, 80.1 g (25.6 mmol) of OH-PDMS was added to a 250 mL three-necked reaction flask equipped with a gas inlet, an air-cooled condenser supplied to an oil bubbler, a glass stopper, and a magnetic stirring rod. While mixing, 4.51 g (19.9 mmol) of BAA1 was added to the OH-PDMS mixture and stirred for about 5 minutes. The atmosphere was inactivated to less than 0.3% oxygen. Next, 10.4 g (54.9 mmol) of 1,1,3,3,-tetramethyl-2-oxa-7-aza-1,3-disilacycloheptane was added to the mixture, resulting in a mild exothermic reaction indicating the reaction. After the exothermic reaction subsided, the mixture was stirred at ambient temperature for 2 hours, at which point the mixture became significantly viscous. The pot temperature was then slowly raised to 80°C over 1 hour, followed by heating at 80°C for 3 hours, then at 120°C for 3 hours, and then at 70°C for 2 hours. 1 H and 29 Si NMR spectroscopy and viscosity measurements supported the formation of a material similar to that in Example 1i.
[0110] When a cyclic siloxane (Y) is combined with a bis-silanol-terminated polydiorganosiloxane such that there are less than 2 moles of cyclic siloxane (Y) per mole of silanol (X) on the bis-silanol-terminated polydiorganosiloxane, and the moles of bis-acryloyloxy-alkane (Z) are equal to half the moles of cyclic siloxane (Y), the copolymer is terminated by an OSiOH functional group (rather than having a primary aminopropyl group) (AB), as shown in Scheme 2. n A copolymer was formed. When the copolymer is used in a hair care composition, Z may be selected to be less than Y / 2 to minimize or avoid the possibility of residual acrylates in the copolymer, thereby reducing the amount of amino-functional terminals (AB) in the mixture. n A copolymer can be formed, which has a silanol terminus at one end and an amino functional group at the other end, (AB) n It may contain copolymers. Residual amino-functional ends (AB)n The amount of copolymer can be 0 to <100%, or 0 to 50%, or 0 to 5%.
[0111] [ka]
[0112] In this Example 7, 80.1 g (25.6 mmol) of OH-PDMS was added to a 250 mL three-necked reaction flask equipped with a gas inlet, an air-cooled condenser supplied to an oil bubbler, a glass stopper, and a magnetic stirring rod. While mixing, 4.51 g (19.9 mmol) of BAA1 was added to the mixed OH-PDMS and stirred for about 10 minutes. The atmosphere was inactivated to less than 0.3% oxygen. Next, 7.81 g (41.2 mmol) of 1,1,3,3,-tetramethyl-2-oxa-7-aza-1,3-disilacycloheptane was added to the mixture, resulting in a mild exothermic reaction. After the exothermic reaction subsided, the mixture was stirred at ambient temperature for 1.5 hours, at which point it became significantly viscous. The pot temperature was then raised to 60°C and stirred for 1.5 hours, followed by heating at 80°C for 6 hours to obtain a polymer with a viscosity of 755 mPa·s and an average molecular weight of 19940 g / mol. The product also contained, 1 H, 13 C and 29 Si It was also characterized by NMR spectroscopy.
[0113] In Comparative Example 8, instead of alkanediol acrylates, alkanediol di(meth)acrylates BAA4 and BAA5 were used to attempt the synthesis of the derivative polymers of Reference Examples 1 and 4 under similar conditions. The conversion was extremely slow, taking several weeks even to complete 50% of the conversion. Neither alkanediol(meth)acrylates BAA4 nor BAA5 underwent complete conversion when combined with either TAS1 or TAS2, even when TAS was used in either a 30% or 100% molar excess. Furthermore, the addition of the catalyst, DBU (approximately 2000 ppm), slightly improved the conversion rate, but complete conversion could not be achieved even with a time frame of several weeks with heating to 120°C. Moreover, the process initiation was not equivalent, as inactivating the reaction flask and heating to 60°C for at least less than 1 hour resulted in polymerization of the methacrylate moiety and separation from the polyorganosiloxane matrix, which began with the formation of a turbid white solid. Without a process to remove the methacrylate moiety from the product, these copolymers are unsuitable for any personal care applications due to the skin-sensitizing properties of the methacrylate-functionalized starting materials.
[0114] In this Reference Example 9, emulsions of the copolymer sample prepared as described above were prepared using the starting materials and amounts shown in Table 4 below. The amounts are in weight percent. The sample was prepared as follows: Copolymer, surfactant, and water were added to a 100 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time in a Speed Mixer. The resulting mixture was progressively diluted with the remaining amount of water, and the mixture was mixed at high speed at 3500 RPM for 30 seconds between each sequential water dilution step. Acetic acid was added to this mixture, and the components were further mixed at high speed at 3500 RPM for 30 seconds.
[0115] [Table 4]
[0116] In this Reference Example 10, emulsions of the copolymer sample prepared as described above were prepared using the starting materials and amounts shown in Table 5 below. The sample was prepared as follows: Copolymer, surfactant, and water were added to a 100 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a Speed Mixer. The resulting mixture was progressively diluted with the remaining amount of water, and mixed at high speed for 30 seconds at 3500 RPM between each sequential water dilution step. Emulsions were prepared using nonionic surfactants. The surfactants used were S1 and S2 in Table 6.
[0117] [Table 5]
[0118] In this reference example 11, emulsions were prepared using anionic, cationic, and nonionic surfactants. The starting materials used are shown in Table 6.
[0119] [Table 6]
[0120] Emulsion samples were prepared using the starting materials listed in Tables 7 and 8 in the following quantities. Unless otherwise specified, the quantities of each starting material are in parts by weight. Table 7 shows nonionic emulsions. Table 8 shows anionic and cationic emulsions.
[0121] [Table 7]
[0122] [Table 8]
[0123] In Tables 7 and 8, "ND" means that no detection was found.
[0124] In Table 7, emulsion EM12 was prepared as follows: 2 g of copolymer P1, 1 g of surfactant S1, and 0.7 g of water (D1) were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a Speed Mixer. 0.1 g of 10% acetic acid solution (A1) was added to the cup, and the contents of the cup were mixed at high speed at 3500 RPM for 30 seconds. The resulting mixture was progressively diluted with water until the final translucent / transparent microemulsion became fluid (had water-like viscosity). 0.5 g of water was added at each step, and the contents of the cup were mixed at high speed in between.
[0125] In Table 7, emulsion EM16 was prepared as follows: 3.59 g of copolymer P3, 0.13 g of surfactant S1, 0.12 g of surfactant S2, and 0.36 g of water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM in a Speed Mixer for 30 seconds each time. Water was added stepwise to the cup with high-speed mixing between each sequential water dilution step until the total water content reached 2.15 g and the resulting emulsion became fluid.
[0126] In Table 7, emulsion sample 17 was prepared as follows: 3.6 g of copolymer P2, 0.13 g of surfactant S1, 0.12 g of surfactant S2, and 0.35 g of water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM in a Speed Mixer for 30 seconds each time. Water was added stepwise to the cup with high-speed mixing between each sequential water dilution step until the total water content reached 2.15 g and the resulting emulsion became fluid.
[0127] In Table 7, emulsions EM21 to EM24 were prepared as follows: Copolymer, surfactant S5, and water (D1) were added to a 100 DAC cup. These starting materials were rapidly mixed at 3500 RPM for 1 minute using a SpeedMixer (Flaktek SpeedMixer DAC 330-100 SE). The resulting mixtures were progressively diluted with the remaining amount of water (D1), with rapid mixing at 3500 RPM for 30 seconds between each sequential water dilution step. A 10% acetic acid solution (A1) was added to the cup, and the contents of the cup were rapidly mixed at 3500 RPM for 30 seconds. Then, surfactant S2 was added to the cup, and the contents of the cup were rapidly mixed at 3500 RPM for 30 seconds.
[0128] In Table 7, emulsion EM25 was prepared as follows: 3.01 g of copolymer P7, 0.15 g of surfactant S1, 0.12 g of S2, and 0.33 g of water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM in a Speed Mixer for 30 seconds each time. Water was added stepwise to the cup with high-speed mixing between each sequential water dilution step until the total water content reached 1.72 g and the emulsion became fluid.
[0129] In Table 8, emulsion EM13 was prepared as follows: 2 g of copolymer P1, 0.29 g of surfactant S1, and 2.23 g of anionic surfactant S3 were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a Speed Mixer. 0.1 g of 10% acetic acid solution (A1) was added to the cup, and the contents of the cup were mixed at high speed at 3500 RPM for 30 seconds. The resulting mixture was progressively diluted with water until the final translucent / transparent microemulsion became fluid (had water-like viscosity). 0.5 g of water was added at each step, and the contents of the cup were mixed at high speed in between.
[0130] In Table 8, emulsion EM14 was prepared as follows: 4.8 g of copolymer P1, 0.24 g of surfactant S1, and 0.76 g of anionic surfactant S3 were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM in a Speed Mixer for 30 seconds each time. Water was added to the cup in stages (totaling 2.21 g) until the resulting emulsion became fluid, and high-speed mixing was performed between each sequential water dilution.
[0131] In Table 8, emulsion EM15 was prepared as follows: 3.6 g of copolymer P3, 0.19 g of surfactant S1, 0.13 g of surfactant S2, and 0.36 g of water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a SpeedMixer (Flaktek SpeedMixer DAC 150.1 FVZ-K). Water was added to the cup in stages until the total water content reached 1.67 g. The resulting product was mixed at high speed between each sequential water dilution step. 0.42 g of cationic surfactant S4 was added to the cup, and the contents of the cup were mixed at high speed at 3500 RPM for 30 seconds.
[0132] In Table 8, emulsion EM18 was prepared as follows: 3.56 g of copolymer P1, 0.2 g of surfactant S1, 0.18 g of surfactant S2, and 0.57 g of water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a Speed Mixer. Water was added to the cup in stages until the total water content reached 1.58 g. The resulting product was mixed at high speed between each sequential water dilution step. 0.4 g of cationic surfactant S4 was added to the cup, and the contents of the cup were mixed at high speed at 3500 RPM for 30 seconds.
[0133] The particle size of macroemulsions (e.g., EM14-EM18 and EM25) was measured using a Malvern Mastersizer 3000. A small amount of emulsion (<1 wt%) was first diluted with DI water. This diluted emulsion was then added dropwise to the Mastersizer's Hydro LV attachment until the obscuration reached 5%-8%. Subsequently, particle size analysis was performed using a custom SOP for particles smaller than 10 μm.
[0134] The particle size of microemulsions (e.g., EM12 and EM13) was measured using a Microtrac® Nanotrac Wave particle size analyzer. Background scattering data was collected by adding DI water to the sample chamber. A small amount of emulsion (<1 wt%) was separately diluted with DI water. This diluted emulsion was then dropped into the sample chamber of the particle size analyzer. Subsequently, particle size analysis was performed using a custom SOP. No particle size was detected for samples EM21-24, likely because the actual size was below the detection limit of the instrument.
[0135] In this Reference Example 12, emulsion samples EM19 and EM20 were prepared as follows, using the starting materials and amounts shown in Table 9 below. The amounts are in parts by weight. The copolymer, surfactant, and first water were added to a 20 DAC cup. These starting materials were mixed at high speed twice at 3500 RPM for 30 seconds each time using a SpeedMixer (Flaktek SpeedMixer DAC 150.1 FVZ-K). Acetic acid (10%) and diluting water were added stepwise to the mixture, and high-speed mixing was performed between each sequential water dilution step.
[0136] [Table 9]
[0137] In this comparative example 13, the aminosilicone emulsion (EM11) was prepared as follows: 57.5 g of bis-diisopropanolamino-PG-propyldisiloxane / bis-vinyldimethicone copolymer, 2.4 g of T Maz-20, and 6 g of water were added to a 100 DAC cup. These starting materials were rapidly mixed twice at 3500 RPM for 30 seconds each time using a Speed Mixer (Flaktek SpeedMixer DAC 150.1 FVZ-K). 12 g of water was added to the cup, and the contents of the cup were rapidly mixed at 3500 RPM in the Speed Mixer. An additional 22 g of water was added to the cup, and the contents of the cup were rapidly mixed at 3500 RPM in the Speed Mixer.
[0138] In this Reference Example 14, a rinse-off hair conditioner formulation (CF) was prepared using the emulsion prepared as described above and the starting materials shown in Table 10 below.
[0139] [Table 10]
[0140] Samples of rinse-off hair conditioner formulations were prepared as follows, using the amounts of each starting material shown in Table 11 below. Deionized water was added to a mixing vessel and heated to 70°C. Moderate stirring was used to diffuse the mixture until the hydroxyethylcellulose was completely dissolved. The temperature was reduced to 60°C, and cetearyl alcohol, PEG-100 stearate, glyceryl stearate, and silicone (if present) were added. The conditioner was mixed for 3 minutes, then tetrasodium EDTA was added and mixed for another 3 minutes. When the temperature fell below 40°C, phenoxyethanol was added. The lost water was replenished, and the resulting formulation was mixed for a further 5 minutes. The final pH of all conditioner formulations was approximately 5.
[0141] For the silicone emulsion, the emulsion was added last along with phenoxyethanol.
[0142] [Table 11]
[0143] [Table 12]
[0144] In Table 11, qs is considered a "sufficient amount".
[0145] A study was conducted to evaluate the ease of combing hair treated with rinse-off hair conditioner formulations (CF1-CF13 above) in both wet and dry states. Slightly bleached Caucasian hair from International Hair Importers was used to test the rinse-off hair conditioner formulations. Each hair clump weighed 2 grams. Each hair clump was rinsed for 30 seconds under running tap water at 40°C. Using a pipette, 0.4 grams of a solution containing 9% sodium lauryl sulfate was applied and lathered over the entire hair clump for 30 seconds. The hair clump was then rinsed under running water for 1 minute. Excess water was removed from each hair clump by passing it between the index and middle fingers of the hand. The hair clump was then treated with one of the rinse-off conditioner formulations from Examples CF1-CF13, at a ratio of 0.4 g of formulation per 1 g of hair, by massaging the formulation into the wet / damp hair for 1 minute. Next, the hair was rinsed with 40°C tap water for 30 seconds. Excess water was removed by pulling the hair through the index and middle fingers. The hair was placed on a tray covered with paper towels and dried at room temperature overnight. The rinse-off hair conditioner samples prepared as described in Reference Example 14 above were tested according to the friction coefficient, INSTRON COMBING, INSTRON WET COMBING, and INSTRON DRY COMBING methods described below. The results are shown in Table 12 below.
[0146] [Table 13]
[0147] [Table 14]
[0148] Comparative Example 1 was a control and did not contain the copolymer or the terminal aminosilicone comparative example. Comparative Examples 2 and 3 contained commercially available aminosilicones instead of the copolymer of the present invention.
[0149] The results in Table 12 show that all examples of the present invention containing copolymers prepared using terminal primary amino-functional siloxanes performed significantly better than the control CF1 in both dry and wet combing. Most of the copolymers of the present invention performed comparably to the commercially available aminosilicones in the comparative examples, while CF13 performed better than the other polymers in dry combing. For COF, all samples performed better than the control CF1.
[0150] In this Reference Example 15, hair care compositions CF17 to CF23 were prepared, and their styling / curl retention was evaluated as follows. CF17 to CF23 were prepared by simply diluting emulsions in deionized water while stirring thoroughly at room temperature. Samples CF17 to CF23 had the amounts of starting materials shown in Table 13 below. The amounts are in parts by weight.
[0151] Tests were conducted to evaluate the styling and curl-holding effects of formulations CF17-CF23 as follows. Slightly bleached Caucasian hair from International Hair Importers was used for the test. Each hair bundle weighed 2 grams. Each hair bundle was rinsed for 30 seconds under running tap water at 40°C. Using a pipette, 0.4 grams of a solution containing 9% sodium lauryl sulfate was applied and lathered over the entire hair bundle for 30 seconds. The hair bundle was then rinsed under running water for 1 minute. Excess water was removed from each hair bundle by passing it between the index and middle fingers of the hand. The hair bundle was then treated with one of samples CF17-CF21, at a ratio of 0.15 g of formulation per 1 g of hair, by massaging the formulation into the wet / damp hair for 1 minute. The hair bundle was tightly wrapped around a curler and left in a 45°C oven overnight. The next day, the hair bundle was removed from the oven and allowed to cool to room temperature for 30 minutes. The curlers were carefully removed from the hair stalks, and the stalks were suspended in a humidity chamber at 25°C and 80% relative humidity for a total of 5 hours. The curl retention rate (%) was calculated based on the length of the hair stalks before incubation in the humidity chamber. The results in Table 13 show that hair treated with CF20 and CF21 provided improved curl retention compared to comparative examples CF17 and CF18, and was comparable to the best silicone product (CF19).
[0152] [Table 15] In Table 13, qs means "sufficient amount". a Used in the comparative example, it is available from DSC under the trade name DOWSIL(trademark)CE-7080 Smart Style.
[0153] [Table 16]
[0154] CF21 contains a copolymer with a longer degree of polymerization (DP) and functions comparably to the comparative example sample CF19. However, the polymer used in CF19 is known to contain high levels of cyclomethicone (>0.1%), which is a concern for personal care applications. The polymers used in CF20 and CF21 retain low levels of cyclomethicone (<0.1%) even after aging at room temperature for two years. Surprisingly, the inventors found that the copolymer of the present invention has the advantage of a lower cyclomethicone content, particularly in samples with siloxanes having a longer DP. When using siloxanes with a shorter DP in the copolymer (CF20-EM19 with siloxanes having 44 DP), a curl-retention effect was also observed compared to the control.
[0155] In this Reference Example 16, hair cohesion was evaluated as follows: Curly hair purchased from International Hair was washed with 9% SLS for 30 seconds and treated with 0.15 g of CF17, CF22, or CF23 per gram of hair. The hair stalks were left at room temperature and 50% relative humidity, and the cohesion coefficient was measured using Bossa Nova RUMBA after 3 hours and 21 hours, with and without combing. The results in Table 15 below show that the hair stalks treated with the present example (CF23) had higher hair cohesion compared to the control under all conditions. Compared to Comparative Example CF22, the hair treated with CF23 showed significantly improved cohesion after 21 hours.
[0156] [Table 17]
[0157] The test methods used in this specification are described below.
[0158] 29 Si NMR and 13 Using 13C NMR spectroscopy, hydrocarbon groups in polydiorganosiloxanes (e.g., the R groups mentioned above) are identified. 8 and / or R 9such as R groups) can be quantified. 29 Si NMR spectra should be obtained using the methodology outlined by Taylor et al. in Section 5.5.3.1, pages 347 to 417, Chapter 12 of *The Analytical Chemistry of Silicones*, edited by A. Lee Smith, Chemical Analysis Vol. 112 (1991) from John Wiley & Sons. In this chapter, the authors discuss inherent general parameters for acquiring quantitative NMR spectra of silicon nuclei. Each NMR spectrometer differs with respect to electronic components, capabilities, sensitivity, frequency, and operating procedures. In the sample 29 Si and 13 To tune, shim, and calibrate a pulse sequence sufficient for quantitative 1D measurement of C nuclei, the instrument manual of the spectrometer used must be consulted.
[0159] An important output of NMR analysis is the NMR spectrum. In the absence of a standard, it is recommended that the signal-to-noise ratio of signal height to average baseline noise be 10:1 or greater to be considered quantitative. A properly acquired and processed NMR spectrum yields signals that can be integrated using any commercially available NMR processing software package.
[0160] From these integrals, the weight percent of total R group content can be determined from 29 the Si NMR spectrum by the following formula (I M )·(U M )=G M ;(I M(R) )·(U M(R’) )=G M(R) ;(I D )·(U D )=G D ;(I D(R) )·(U D(R) )=G D(R) ;U R / U M(R) =Y R’ ;U R / U D(R) =Y R’’; Y R’’ ·[G M(R) / (G M +G M(R) +G D +G D(R) )·100]=W R’ ; Y R’’’ ·[G D(R) / (G M +G M(R) +G D +G D(R) )·100]=W R’’ ; and W R’ +W R’’ =total W R can be calculated, where I is the integrated signal of the indicated siloxy group, U is the unit molecular weight of the indicated siloxy group, G is a placeholder representing the gram unit, W is the weight percent of the indicated siloxy unit, Y is the value of the specified ratio of the siloxy unit, R is as defined above, R' represents the R group solely from M(R), and R ’’ " represents the R group solely from the D(R) group.
[0161] 1 H-NMR was evaluated using a Varian 400MHz Mercury NMR Spectrometer. The sample was prepared by dissolving the analyte in CDCl3, and the CDCl3 accounted for at least 60% but no more than 90% of the mass. The determination of complete conversion of the acrylate component was performed when the vinyl proton signal was not distinguishable from the baseline.
[0162] Using FTIR, (AB) nThe concentration of unreacted acrylates present in the copolymer can be determined. FTIR analysis was performed using a PerkinElmer FTIR Spectrometer Frontier. Samples were prepared by diluting the polymer with tetrachloroethylene and mixing by vortex treatment. After mixing, the samples were pipetted into an FTIR sample cell with a fixed gap between two NaCl salt plates. The sample cell was then placed in the FTIR instrument and scanned 16 times to obtain the final spectrum.
[0163] The viscosity of copolymers can be measured using rheometry. Viscosity measurements were performed on a Brookfield DV-III Ultra Programmable Rheometer fitted with a CPE-44Y standard sample cup incorporating a CPE-52 cone and temperature probe, and calibrated to measure the kinematic viscosity of aminosilicone polymers as described in the manual. Approximately 0.4 mL of sample was poured into the center of the sample cup, and the sample cup was set in place for measurement. The appropriate RPM value was determined by confirming that the cup temperature was 25°C, examining the % torque, and adjusting the RPM value as necessary.
[0164] GPC can be used to measure the number-average molecular weight (Mn) and weight-average molecular weight (Mw) of copolymers. The measurements were performed using the system described in the table below. Samples were prepared at a concentration of 10 mg / mL in 20 mL scintillation vials and capped with acetic anhydride. After shaking the samples using a list shaker for 2 hours, they were filtered through a 0.45 μm PTFE syringe filter into 2 mL GC vials. The samples were placed on an autosampler and data acquisition was started. Data acquisition was performed over 30 minutes, the data were processed, and analyzed against polystyrene standards ranging from 580 to 2,750,000 daltons.
[0165] [Table 18]
[0166] The coefficient of friction (COF) is an industry standard method for measuring the decrease in the frictional properties of a treatment on hair, and it correlates with subjective counts of smoothness and flexibility. For testing in a temperature and humidity-controlled room, a Diastron MTT175 tensile testing machine with a rubber probe fitted with a 50g normal force was used. Three hair bundles per treatment, and five measurements per hair bundle, were tested to obtain friction data in both the direction of the hair cuticle and the reverse direction. The coefficient of friction (COF) is given by F / N, where F is the outward force and N is the normal force. The same hair bundles used in the comb-through test were used to measure the coefficient of friction in a dry state.
[0167] An INSTRON Model 4464 running BlueHill 2 software was also used to measure conditioning performance based on the ease of combing when wet and when dry. The tests utilized INSTRON strain gauges, which are equipped to measure the force required to comb the hair. Conditioning performance was based on the ability of a specific hair treatment formulation, such as a shampoo or hair conditioner, to reduce the force required to comb the hair using the INSTRON strain gauges. The force was reported as mean comb load (ACL). A lower ACL value indicated a greater conditioning effect from the formulation being tested.
[0168] Following the INSTRON WET COMBING method, the hair was first wet by dipping it in distilled water, and then detangled by combing the hair three times. Next, the hair was detangled again by dipping the hair three times in distilled water. Excess water was removed from the hair by passing it twice between the index and middle fingers. The hair was placed on a hanger and combed with an INSTRON comb. The process of detangling and combing was repeated until all data points were collected. The average combing force of the three hair sections was measured for each treatment.
[0169] Following the INSTRON DRY COMBING method, hair tangles were loosened by combing a section of hair three times. Next, the hair section was tangled again by rotating it three times clockwise and three times counterclockwise. The hair section was placed on a hanger and combed with an INSTRON comb. This process of tangling and combing was repeated until all data points were collected. The average combing force of the three hair sections was measured for each treatment.
[0170] Industrial applicability The copolymers described herein may have one or more of the following advantages: low cyclic polyorganosiloxane content (<0.05% octamethylcyclotetrasiloxane), post-aging stability as demonstrated by the low cyclic content after aging, little to no crosslinking, and potential for biodegradability. Furthermore, the copolymers may be miscible with organic solvents and some oils. Although we do not wish to be constrained by theory, it is thought that copolymers having a subscript a of at least 44, or 44-200, or 44-84 may provide improved curl retention when incorporated into hair styling compositions. Although we do not wish to be constrained by theory, copolymers having longer chains (e.g., containing >6 carbon atoms, or 10 or more carbon atoms) D Furthermore, it is conceivable that the performance of the copolymer on hair may be improved, particularly in the dry combing test described above. As shown by the above examples, the copolymer of the present invention also provides significantly better wet combing performance than terminal aminosilicone polymers, using the wet combing test described above.
[0171] The copolymers described herein are useful for hair care applications and may provide one or more styling benefits, such as increased curl retention, improved hair cohesion, and / or improved hair orientation and / or hair conditioning, as evidenced by improved dry and / or wet combing performance and an improved coefficient of friction. This application also relates to the following aspects. [1] Mode:
change
change
change
change
change
change
[0172] Definitions and Use of Terms All quantities, ratios, and percentages are by weight unless otherwise indicated in the context of the specification. The total amount of all starting materials in a composition is 100% by weight. The "Summary of the Invention" and the "Abstract" are incorporated herein by reference. The articles "a," "an," and "the" each refer to one or more unless otherwise indicated. The singular form includes the plural form unless otherwise indicated. The terms "comprising" and "comprise" are used herein in their broadest sense to mean and encompass the ideas of "including," "include," "consisting essentially of," and "consisting of." The use of "for example," "eg," "such as," and "including" to list examples is not limited to the examples listed. Therefore, “for example” or “such as” means “for example, but not limited to” or “such as, but not limited to,” and includes other similar or equivalent examples. A disclosure of a scope includes the scope itself and anything contained within it, as well as its endpoints. Similarly, a disclosure of a Markush group includes the entire group, as well as any individual elements and subgroups contained therein. For example, a disclosure of the Markush group “hydrogen atom, alkyl group, alkenyl group or aryl group” includes the individual alkyls that are its elements, the alkyl and aryl subgroups, and any other individual elements and subgroups contained within the Markush group. Abbreviations are as defined in Table 7 below.
[0173] [Table 19]
Claims
1. formula: 【Chemistry 1】 [In the formula, each R 1 This is a monovalent hydrocarbon group consisting of 1 to 12 carbon atoms, which are independently selected. Each R E These are independently hydroxyl and H 2 N-R A Selected from the group consisting of the amino functional groups, Each R A These are independently divalent hydrocarbon groups consisting of 1 to 12 carbon atoms. Each R 2 These are independently selected from the group consisting of hydrogen and methyl, Each R D This is a divalent hydrocarbon group of 2 to 20 carbon atoms, which is independently selected. Each subscript 'a' independently has a value such that 0 ≤ a < 220. The subscript b has a value such that 1 ≤ b ≤ 100. Aminosiloxane ester copolymers containing these polymers.
2. If one or more of conditions i) to vii) are met, Condition i) is that the subscript 'a' is between 2 and 200. Condition ii) is that the subscript b is between 2 and 20. Condition iii) is each R D It has 3 to 12 carbon atoms. Condition iv) is that each R 2 is hydrogen, Condition v) is, each R 1 It is an alkyl group with 1 to 6 carbon atoms. Condition vi) is, each R A However, it is an alkyl group with 1 to 6 carbon atoms. Condition vii) is that the copolymer has a number-average molecular weight of >1,000 g / mol to 250,000 g / mol as measured by gel permeation chromatography. The copolymer according to claim 1.
3. A process for preparing the copolymer according to claim 1, wherein each R E is an amino functional group, and the process is, (A) Formula 【Chemistry 2】 A terminal primary amino-functional polyorganosiloxane, wherein each R 1 This is a monovalent hydrocarbon group consisting of 1 to 12 independently selected carbon atoms, and each R A Independently, is a divalent hydrocarbon group of 1 to 12 carbon atoms, where the subscript a has a value such as 0 ≤ a < 220, terminal primary amino-functional polyorganosiloxane, and (B) Formula 【Transformation 3】 A bis-acryloyloxy-alkane in which R D This involves combining starting materials containing bis-acryloyloxyalkanes, which are divalent hydrocarbon groups with 2 to 20 carbon atoms. A process for preparing a copolymer, wherein the starting material (A) and starting material (B) are present in amounts such that the molar ratio of (A):(B) is in the range of 2:1 to 1:
1.
4. A copolymer preparation process according to claim 1, wherein the process is: 1) (B) Formula 【Chemistry 4】 A bis-acryloyloxy-alkane in which R D These are bis-acryloyloxyalkanes, which are divalent hydrocarbon groups with 2 to 20 carbon atoms. (F) formula 【Transformation 5】 A bis-silanol-terminated polydiorganosiloxane in which R 1 is a monovalent hydrocarbon group of 1 to 12 independently selected carbon atoms, where the subscript a independently has a value such that 0 ≤ a < 220, a bis-silanol-terminated polydiorganosiloxane. (G) Formula 【Transformation 6】 A cyclic siloxane in which the subscript c is 0 or 1, and each R 8 R is a monovalent hydrocarbon group consisting of 1 to 18 carbon atoms, which are independently selected. 9 This is a cyclic siloxane, independently selected from the group consisting of hydrogen and an alkyl group with 1 to 15 carbon atoms. A copolymer preparation process, which involves combining starting materials containing [a specific substance].
5. (B) The process according to claim 3 or claim 4, wherein the bis-acryloyloxyalkane is selected from the group consisting of 1,3-butanediol diacrylate, 1,4-butanediol diacrylate; 1,6-hexanediol diacrylate; 1,9-nonanediol diacrylate, 1,10-decanediol diacrylate, and two or more combinations of 1,3-butanediol diacrylate, 1,4-butanediol diacrylate; 1,6-hexanediol diacrylate; 1,9-nonanediol diacrylate, and 1,10-decanediol diacrylate.
6. The process according to claim 3 or 4, further comprising adding (C) a catalyst, (D) a solvent, (E) an acrylate polymerization inhibitor, and additional starting materials selected from the group consisting of two or more combinations of (C), (D), and (E) during step 1).
7. The process according to claim 3 or 4, wherein one or both of conditions (a) and (b) are met, wherein the combination in step 1) comprises mixing and heating the starting materials at a temperature of 0°C to 180°C, and condition (b) is that the combination in step 1) is carried out for 1 to 48 hours.
8. 2) The process according to claim 3 or 4, further comprising recovering the copolymer during and / or after step 1).
9. The process according to claim 4, wherein the method uses less than 2 molar equivalents of (G) a cyclic siloxane per mole of (F) a bis-silanol-terminated polydiorganosiloxane.
10. The process according to claim 4, wherein (F) a cyclic siloxane is used in an amount of 2 molar equivalents or more per mole of bis-silanol-terminated polydiorganosiloxane.
11. It is an emulsion, (I) A liquid continuous phase containing water (II) An emulsion comprising a discontinuous phase dispersed in the liquid continuous phase, wherein the discontinuous phase comprises the aminosiloxane ester copolymer described in claim 1 or claim 2.
12. The emulsion according to claim 11, further comprising (H) a surfactant, (I) an acid compound, (J) an acid anhydride, (K) a thickener, (L) a stabilizer, and additional starting materials selected from the group consisting of two or more combinations of (H), (I), (J), (K), and (L).
13. A method for producing an emulsion, comprising mixing a copolymer according to claim 1 or claim 2, water, and a starting material optionally selected from the group consisting of (H) a surfactant, (I) an acid compound, (J) an anhydride, (K) a thickener, and (L) a stabilizer, under shear pressure.
14. Use of the copolymer according to claim 1 or claim 2 in a hair care composition.
15. The use according to claim 14, wherein the hair care composition is a conditioner or a styling product.
Citation Information
Patent Citations
Amino-containing polysiloxane-acrylic ester and preparation method and application thereof
CN106750318A
Radiation curing organosilicon compound and strippable cured film consisting of cured article thereof
JP1985190427A
Acrylic functional silicone compound
JP1987158723A
Production of releasable cured film composed of cured matter of organosilicon compound
JP1995008908A
Acrylic-functional siloxane
JP1995316302A
